Evaluation of the Utilization of Health Services at the Sekotong Community Health Center in a Review of the New Public Service (NPS) Theory - Niswatun Junardi; Nur Indah Safitri; Safirah Hairunnisah; Riri Anggriani; Rasta Aprilia; Safiratul Adawyah; Rahmad Hidayat (JURNAL ILMIAH DETUBUYA, 2025)
Public service represents the government’s responsibility to fulfill citizens’ basic needs through the provision of goods, services, and administrative assistance in accordance with legal regulations. In the context of healthcare, Community Health Centers (Puskesmas) play a vital role as the frontline of public service aimed at improving community health standards. This study examines the implementation of public service at Puskesmas Sekotong from the perspective of the New Public Service (NPS), which emphasizes participatory, collaborative, transparent, and citizen-oriented principles. The findings show that Puskesmas Sekotong has implemented a digital-based service system through the Sehat Indonesiaku (ASIK) application to enhance administrative efficiency and data accuracy, with approximately 60–70% of reports being submitted digitally. Between 2023 and 2025, the total number of patients increased from 9,900 to 10,950, with the most common illnesses being acute respiratory infections (ARI), diarrhea, hypertension, and diabetes, indicating a growing demand for healthcare services. However, several challenges remain, including data integration issues, limited facilities (particularly the lack of a funeral ambulance), and low public awareness of preventive healthcare. Efforts to improve service quality are carried out through human resource development, optimization of facilities and infrastructure, and active community participation in posyandu (integrated service posts), village deliberations, and health cadres. Overall, Puskesmas Sekotong has successfully reflected the core principles of the New Public Service, prioritizing transparency, accountability, and collaboration in delivering inclusive and equitable digital-based public healthcare services.